Enacting Single-Bite-Size Strategy for Learning Disabled as Graduation Requirement through Test of English Proficiency: An Indonesian Context - Widowati, Diah Retno; Prasetyoningsih, Luluk Sri Agus; Hidayanti, Ika; Purnawan, I Kadek; Mei, Lick Cheok (Universitas Negeri Malang, 2023)
It has been for years that Indonesian education institutions rely on foreign language tests to assess students for their admission and graduation requirements. One of the instruments used is Test of English Proficiency (TEP) due to its validity, reliability, objectivity, and its unbiased characteristics to measure students’ ability in English competence. Although studies on the use of TEP have been extensively carried out, little is known about the use of such a test by students with disabilities. To fill the gap, the present study was conducted to investigate the experiences of students with disabilities in learning the TEP preparation using the Single-Bite-Size (SBS) strategy. Data were gathered through an in-depth interview with students with disabilities. The queries raised were about the participants’ problems in learning English, feeling after the implementation of SBS, the experience in taking TEP, and the experience in joining the TEP preparation program. The narrative analysis showcases that promoting SBS strategy in the TEP preparation teaching program could assist students improve their materials comprehension. The study also unpacks that their personalized learning much occurred in the classroom.